Single-port robot-assisted pyeloplasty through supine anterior retroperitoneal access - Sina Sobhani; Sij Hemal (Indian Journal of Urology)
This video explores the technique of robot-assisted pyeloplasty using the Da-Vinci Single-Port robot through the supine anterior retroperitoneal access in a 28-year-old male with a right-sided ureteropelvic junction obstruction. The patient was placed in a supine position, with a 10°–20° elevation of the ipsilateral flank. Retroperitoneal access was obtained at the McBurney’s point for the placement of the port. The standardized steps of the Anderson–Hynes pyeloplasty technique were executed. Operative time was 120 min with 10 mL of blood loss. The patient was discharged on the same day without complications. At 4-months follow-up, on the renal scan, the right kidney showed stable function with improved drainage.